EVALUASI PENGENDALIAN BIAYA PRODUKSI GUNA MENINGKATKAN EFISIENSI BIAYA PRODUKSI PADA CV. CITRA SARI MAKASSAR - Andi Rustam; Faidul Adzim; Andi Ummi Alifah (Jurnal Riset Perpajakan: Amnesty, 2019)
Research aims to know the evaluation of production cost control to increase the efficiency of production costs in CV. Citra Sari Makassar.  This research uses the method of analysis of variance where the company data about the production process and other data that support the research is collected then the data is done analysis by describing and Compare with the data collected, and do the calculation process by comparing between the standard cost and actual cost. This research Data is derived from a direct interview with related parties, documentation, library review, and access to the Web and related sites. The research object is CV. Citra Sari Makassar. The results showed that there was control of production costs by comparing between standard cost and actual cost on CV. Citra Sari Makassar can reach a target of more efficient production cost.